PENGARUH LABA PER SAHAM, DIVIDEN PER SAHAM DAN TINGKAT SUKU BUNGA TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN & MINUMAN DAN PERBANKAN YANG TERDAFTAR DI BEJ TAHUN 2003-2005 - Mardiana, Lilik (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2006)
In modern period like this now, invest is activity that became trend for bisnis sociaty. Other that to invest in stock type. Thera are two method that can use to analysis price of stock, fundament analysis and technical analysis. According to fundamental analysis, a stock has intrinsik value that may influenced by factor interim company, industry and that too conditional of macro economy. Dividend per share to indicate proceed of fund stake holder. Dividend per she to show distribution of net income direct way to stake holder and this dividend by investor to represent information for predicte kinerja of firm to future. If rate interest deposit is high then sociaty will to tend invested to stock than deposit. This examination will to prove influence earning per share, dividend per share and rate interest to price of stock. Sample of examination is food & beverage firm, perbankan that go public in BEI period 2003 -2008.